2009
DOI: 10.1097/pcc.0b013e3181b8088b
|View full text |Cite
|
Sign up to set email alerts
|

Building trust through communication in the intensive care unit: HICCC*

Abstract: Communication is vital to building trust in the pediatric intensive care unit. Developed from parents' own observations and perspectives, HICCC is an accessible framework that can help doctors to remember what parents value in communication in the acute care setting. In addition, pediatric intensivists would benefit from targeted cultural competency training to reduce physician bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 22 publications
0
61
1
Order By: Relevance
“…Parents seek honest, clear, and complete information 42,4450 to be able to actively participate in decision- making 47,51 and in the physical care and comfort to their child, 43,44,47 as well as to cope with uncertainty and fear of a poor outcome.. 42,49,52 Access to information can make parents feel more prepared, less helpless, and give them a sense of control. 42,44,49,52 Parents reported that they wanted to receive information even when it was potentially distressing 42,43,53 and wanted to be informed about decisions even when clinicians are the primary decision-makers.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…Parents seek honest, clear, and complete information 42,4450 to be able to actively participate in decision- making 47,51 and in the physical care and comfort to their child, 43,44,47 as well as to cope with uncertainty and fear of a poor outcome.. 42,49,52 Access to information can make parents feel more prepared, less helpless, and give them a sense of control. 42,44,49,52 Parents reported that they wanted to receive information even when it was potentially distressing 42,43,53 and wanted to be informed about decisions even when clinicians are the primary decision-makers.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…8,16 They serve as educators by interpreting medical information and facilitating communication between physicians and family. 17 The purpose of this study is to describe PICU nurses’ perceptions of the benefits and challenges of providing FCC, given the policy and practice changes needed to facilitate FCC in PICUs.…”
mentioning
confidence: 99%
“…Despite this lack of a prior relationship between the intensive care physician and the family member, decisions that represent a refocusing of care goals were made during or shortly following these conferences, highlighting the importance of establishing trust during these meetings. Delemos et al (28) demonstrated that families of children in the PICU valued trust in PICU physicians and reported that communication was vital to building that trust. Physician-family communication in medical care outside of the ICU depends heavily on prior relationships and continuity of care (29,30).…”
Section: Discussionmentioning
confidence: 98%